Strategi Kelembagaan Tim Pemenangan Rahmat Mirzani Djausal dan Jihan Nurlela dalam Pemilihan Gubernur Lampung 2024 - Akbar Aziz Pratama; Arizka Warganegara; Robi Cahyadi Kurniawan (Universitas Medan Area, 2026)
This article aims to analyze the institutional strategy of the winning team of Rahmat Mirzani Djausal and Jihan Nurlela in the 2024 Lampung Gubernatorial Election. The problem is focused on how networks of political parties, customary community organizations, and religious organizations were established and synergized to secure electoral victory. To address this issue, the study applies the network institutionalism theory, which emphasizes the importance of relationships between formal and informal actors in local political processes. The data were collected through in-depth interviews with representatives of supporting political parties, customary leaders, religious figures, election organizers, and political observers, complemented by observation and document analysis. The data were qualitatively analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the victory of Rahmat Mirzani Djausal and Jihan Nurlela was strongly influenced by the successful integration of political party machinery, social legitimacy from customary institutions, and moral as well as electoral mobilization by religious organizations. This study concludes that an integrated network-based institutional strategy is a decisive factor in winning the 2024 Lampung gubernatorial election and plays a significant role in strengthening the effectiveness of local political mobilization.